Kajian tahap kepuasan penghuni terhadap fasiliti penjara - Nasir, Munirah (2013)
Prison mission on Prison Department of Malaysia Official Portal is to protect society by providing safety detention and effective rehabilitation programs. Although a variety of rehabilitation programs have been carried out in the prison as convicts, but the problem still occurs. Based on one of the news in newspaper recently, the police are trying to locate the former prisoners who are active again in the crime. Therefore, there are rehabilitation programs in prison should be reviewed. Two factors contributed to the success of the rehabilitation program are the programs that provided by the prison and the facilities in a prison. Facilities in a prison should be reassessed to improve prison buildings in Malaysia. Therefore, this study was undertaken to examine the level of satisfaction prison occupants to facilities focused on Sungai Udang Correctional Facility Complex, Malacca. 60 respondents were involved in this study that included prison officers and prisoners. Frequency analysis and descriptive analysis were used in this study to analyse the data. The result of the analysis shows that the criteria are needed in prison. Hopefully this study can help people in the planning and construction to build new prison in the future.